2020
DOI: 10.26434/chemrxiv.12673736.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of the Silica/Divalent Electrolyte Interface: Molecular Insight into Charge Inversion with Increasing pH

Abstract: The molecular origin of overcharging at mineral oxide surfaces remains a cause of contention within the geochemistry, physics, and colloidal chemistry communities owing to competing “chemical” vs “physical” interpretations. Here, we combine vibrational sum frequency spectroscopy and streaming potential measurements to obtain molecular and macroscopic insights into the pH-dependent interactions of calcium ions with a fused silica surface. In 100 mM CaCl<sub>2</sub> electrolyte, we observe evidence o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
2
4
0
Order By: Relevance
“…The resonant vibrational SFG experiments attributed these trends to displacement of the hydration layer above the silica surface by ions retaining their centrosymmetric hydration shell. 55 These trends were attributed to close association of Ca 2+ to the interface, 55,[57][58][59][60][61][62] a finding that would be consistent with the non-resonant c (2) estimates reported here (as well as the largest reduction in interfacial potential by CaCl2 relative to NaCl).…”
Section: B Estimated Trends Insupporting
confidence: 75%
See 2 more Smart Citations
“…The resonant vibrational SFG experiments attributed these trends to displacement of the hydration layer above the silica surface by ions retaining their centrosymmetric hydration shell. 55 These trends were attributed to close association of Ca 2+ to the interface, 55,[57][58][59][60][61][62] a finding that would be consistent with the non-resonant c (2) estimates reported here (as well as the largest reduction in interfacial potential by CaCl2 relative to NaCl).…”
Section: B Estimated Trends Insupporting
confidence: 75%
“…[47][48][49] We therefore find experimental evidence for a significant change in interfacial structure with increasing surface coverage for some of the ions we surveyed, consistent with reports by others for mica:water [50][51][52][53] and silica:water [47][48][49]54 interfaces. Previous studies of divalent cations, specifically magnesium and calcium, by Gibbs and co-workers, 55,56 have shown that low concentrations of these salts (0.033mM) attenuate the vibrational sum frequency generation Ma and Geiger 10 (SFG)-resonant water signal in comparison to NaCl at similar concentrations albeit at a higher pH than the conditions studied here. The resonant vibrational SFG experiments attributed these trends to displacement of the hydration layer above the silica surface by ions retaining their centrosymmetric hydration shell.…”
Section: B Estimated Trends Inmentioning
confidence: 55%
See 1 more Smart Citation
“…The relatively sharp feature observed at ~3670 cm -1 provides additional support for the charge inversion at high YCl3 concentrations. The high-frequency band is located in a similar frequency range as that observed for the OH stretches of Si-OH, Al-OH, and Ca-OH at the aqueous interface with silica, [43,79] alumina, [80] and calcium fluoride, [81] respectively. Thereby, it is assigned to the OH stretch of an yttrium hydroxide cation (i.e.…”
Section: Targetting Interfacial Water Molecules To Detect the Charge Reversion Of The Surfacesupporting
confidence: 62%
“…In summary, we determined the effect of ionic strength on the SFG spectra of the surfacebound waters at the silica/water interface through deconvolution of the spectra into surface-bound water, or (2) , and diffuse layer water, or (3) 3 , components. In lieu of a calculated surface potential for the analysis, we obtained the zeta potential from streaming current measurements, which has been related to both SFG [77][78] and SHG, [79][80][81] but not used to deconvolute the (2) and (3) contributions. With the reported phase-sensitive SFG 32 and SHG 31 measurements of the silica/water interface as reference, we applied the maximum entropy method to our measured SFG intensities to obtain the complex SFG spectra.…”
Section: Discussionmentioning
confidence: 99%